Milk production and composition of dairy cows grazing elephant grass under two grazing intervals - Voltolini, Tadeu Vinhas; Santos, Flávio Augusto Portela; Martinez, Junio Cesar [UNESP]; Imaizumi, Hugo; Clarindo, Rafael Luis; Penati, Marco Antonio (FapUNIFESP (SciELO), 2010)
The objective of this study was to evaluate two grazing intervals (IG) for elephant grass (Pennisetum purpureum Schum cv. Cameroon) pasture: one variable, determined by the entry of animals to the paddocks when 95% of active photosynthetic radiation was intercepted by the sward, and fixed 26-day grazing interval. Eight dairy cows were used, averaging 124 days lactation, 516 kg body weight and 17.5 kg daily milk production at the beginning of the trial. The experimental period was 80 days divided into four sub-periods of 20 days each. Data were analyzed in a cross-over design. The grazing frequencies did not influence milk production and composition, plasma urea nitrogen, body condition score and variations in body weight. However, the stocking rate and milk production per hectare were higher for pasture with interval of grazing determined by 95% of active photosynthetic radiation. Thus grazing frequency defined in variable intervals by sward interception of active photosynthetic radiation result in higher milk production per area unit. © 2010 Sociedade Brasileira de Zootecnia.
Produção e composição do leite de vacas mantidas em pastagens de capim-elefante submetidas a duas frequências de pastejo
Keywords: Dairy cows; Forage; Grassland; Milk production; Pasture management; Pennisetum purpureum